1998
DOI: 10.1016/s0168-6496(98)00010-5
|View full text |Cite
|
Sign up to set email alerts
|

Vertical models of phototrophic bacterial distribution in the metalimnetic microbial communities of several freshwater North-American kettle lakes

Abstract: The composition and the structure of the metalimnetic communities of phototrophic microorganisms were studied in 24 lakes of Wisconsin and Michigan (USA), during the period of summer stratification, and related to environmental parameters. The presence of phototrophic bacteria was reported for the first time in some lakes. Different types of phototrophic microorganisms were separated in three different clusters, by decreasing values of photosynthetic available radiation (PAR) and redox potential (Eh): (1) cyan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 14 publications
4
20
0
Order By: Relevance
“…The positive correlation between NH 4 + ‐N of the porewater and the abundance of Chlorobi is consistent with the data of Edberg, Andersson, and Holmstrom () and suggests these bacteria may have participated in the transformation of NH 4 + ‐N. Additional factors affecting the presence of Chlorobi in mesotrophication regions (A‐3) may include environmental factors because Chlorobi are photosynthetic bacteria and hence require the presence of adequate light penetration in water (Vila, Abella, Figueras, & Hurley, ). On the contrary, Region A‐3 is teemed with a great many submersed vegetation or aquatic plants.…”
Section: Discussionsupporting
confidence: 83%
“…The positive correlation between NH 4 + ‐N of the porewater and the abundance of Chlorobi is consistent with the data of Edberg, Andersson, and Holmstrom () and suggests these bacteria may have participated in the transformation of NH 4 + ‐N. Additional factors affecting the presence of Chlorobi in mesotrophication regions (A‐3) may include environmental factors because Chlorobi are photosynthetic bacteria and hence require the presence of adequate light penetration in water (Vila, Abella, Figueras, & Hurley, ). On the contrary, Region A‐3 is teemed with a great many submersed vegetation or aquatic plants.…”
Section: Discussionsupporting
confidence: 83%
“…in June, August and October). At these times, they were distributed over the whole chemocline and thus encountered in a light intensity range from high to low and, similar to reports for other meromictic lakes [38], they were present at the same depths as purple sulfur bacteria. Populations of purple sulfur bacteria, however, were microstratified under these conditions.…”
Section: Discussionsupporting
confidence: 84%
“…In addition to other physico‐chemical conditions such as higher redox potential, higher oxygen or sulfide concentrations reported to favor growth of purple sulfur bacteria over that of certain green sulfur bacteria [38,43], metabolic properties might give purple sulfur bacteria growth advantages over green sulfur bacteria. Small‐celled purple sulfur bacteria in the chemocline of Lake Cadagno form large cell aggregates with up to 900 cells and are associated with sulfate‐reducing bacteria related to the genus Desulfocapsa [18].…”
Section: Discussionmentioning
confidence: 99%
“…To examine this idea and to identify similarities between Cross Reservoir and naturally occurring lakes that contain significant populations of ‘ C. aggregatum ’, we compiled a list of the basic characteristics of 12 lake systems along with important lake information such as trophic status, mixing status and sulphide and light levels at the depth of the consortia (Table 5). Studies of other lakes have revealed dense plates of ‘ C. aggregatum ’ and/or other species of PSB (Takahashi & Ichimura, 1968; Czeczuga & Gradzki, 1973; Moffett, 1991; Vila et al. , 1998), but are not included in this table because their physicochemical profiles were not fine enough to characterise the zone of the consortia, detailed bacterial identifications were not performed, or because other important lake parameters were unavailable.…”
Section: Cross Reservoir Compared With Natural Lake Systemsmentioning
confidence: 99%
“…DCM are typically comprised of locally dense, subepilimnetic communities of photosynthetic bacteria and/or algae. After years of focus on phytoplankton in DCM, a growing body of research has revealed that deep layers of both purple and green photosynthetic sulphur bacteria (PSB) may be of equal or greater importance to the lake system (Parkin & Brock, 1980; Vila et al. , 1998).…”
Section: Introductionmentioning
confidence: 99%